Analisis Sarana Dan Prasarana Pada Ruang Filing Terhadap Keamanan Berkas Rekam Medis Di Puskesmas Wadaslintang 1 - Anis Nurhaliza (Jurnal Infokes, 2021)
Security and privacy are very inportant factors in the administration of clinical record just as secyrity in the capacity room.The documenting room is one of the significant perspectives in the puskesmas or clinic, particularly clinical records,the kind of exploration utilized is expressive subjective research,which is an examination technique completed with the principle point of making an elucidating or enlightening of a circumstance unbiasedly by gathering information throught perception and quetonnaire methods.The subjects in this review were clinical record officials at the wadaslintang 1 distribute wellbeing focus by giving a few questionnare. there are a few deficiencies in the documenting room at the Wadaslintang 1 wellbeing community including, , there is no cctv to screen the documenting room, there is no cooling to control the room temperature in the occupying room, the racks are too thin with the goal that clinical records are some of the time hard to get in and out of the recording rack. The reason for this review is to manage what offices and framework ought to be contained in the documenting room of the Wadaslintang Wellbeing Center 1. This exploration is subjective utilizing the perception technique. wadaslintang 1 wellbeing community as per the guidelines of the Pastor of Wellbeing R1.